2018
DOI: 10.1016/j.neures.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes regulating GABAergic interneuron maturation

Abstract: During embryonic development, GABAergic interneurons, a main inhibitory component in the cerebral cortex, migrate tangentially from the ganglionic eminence (GE) to cerebral cortex. After reaching the cerebral cortex, they start to extend their neurites for constructing local neuronal circuits around the neonatal stage. Aberrations in migration or neurite outgrowth are implicated in neurological and psychiatric disorders such as epilepsy, schizophrenia and autism. Previous studies revealed that in the early pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…A few of our KO lines target genes having human orthologs that share a GWAS BMI cluster with other genes linked to obesity. Genes for the kinase Dgkg 188 and the neuronal membrane protein Lrrn2 189 have no publicly available KO data or published links to obesity despite having increased body fat in our HTS ( Table 7 ). DGKG and ETV5 (ETS variant transcription factor 5) are the only genes sharing a BMI cluster on human chromosome 3, while LRRN2 and MDM4 (MDM4 regulator of p53) are the only genes sharing a BMI cluster on human chromosome 1 ( Table 8 ); the low body fat observed in Etv5 KO mice 190 and Mdmx KO mice 191 suggests that one or both genes in each of these two BMI clusters may contribute to the GWAS signal.…”
Section: Resultsmentioning
confidence: 99%
“…A few of our KO lines target genes having human orthologs that share a GWAS BMI cluster with other genes linked to obesity. Genes for the kinase Dgkg 188 and the neuronal membrane protein Lrrn2 189 have no publicly available KO data or published links to obesity despite having increased body fat in our HTS ( Table 7 ). DGKG and ETV5 (ETS variant transcription factor 5) are the only genes sharing a BMI cluster on human chromosome 3, while LRRN2 and MDM4 (MDM4 regulator of p53) are the only genes sharing a BMI cluster on human chromosome 1 ( Table 8 ); the low body fat observed in Etv5 KO mice 190 and Mdmx KO mice 191 suggests that one or both genes in each of these two BMI clusters may contribute to the GWAS signal.…”
Section: Resultsmentioning
confidence: 99%
“…The differential splicing and over-expression of an ADP-ribosylation factor-like protein 4D (ARL4D) isoform (Figure 2) in MIA relative to control weaned males (27.9%) is aligned with the over-expression of ARL4D in the cerebral cortex GABAergic neurons of mice heterozygous for GAD67-GFP knock-in line that presents ADHD and ASD-like behaviors [99]. Likewise, the differential alternative splicing detected in neurocan (NCAN) could be connected with mutations in this gene associated with SSD and bipolar disorder [100].…”
Section: Differential Alternative Splicing Associated With Maternal I...mentioning
confidence: 92%
“…Ezh2 has been suggested as a relevant TF for oligodendrocytes, and the expression of Ezh2 in OPCs (oligodendrocytes precursor cells), even up to the stage of pre-myelinating immature oligodendrocytes, remains high ( Copray et al, 2009 ) ( Figure 6C ). Furthermore, the MultiCapsNet found that Rpp25 is strongly associated with interneurons which SCENIC did not, and Rpp25 has been reported up-regulated in GABAergic interneuron ( Fukumoto et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%